2020
DOI: 10.1021/acs.chemmater.0c02296
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Orientation Dependent Oxidation Modes at the Buried Graphene–Cu Interface

Abstract: We combine spatially resolved scanning photoelectron spectroscopy with confocal Raman and optical microscopy to reveal how the oxidation of the buried graphene–Cu interface relates to the Cu crystallographic orientation. We analyze over 100 different graphene covered Cu (high and low index) orientations exposed to air for 2 years. Four general oxidation modes are observed that can be mapped as regions onto the polar plot of Cu surface orientations. These modes are (1) complete, (2) irregular, (3) inhibited, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 114 publications
1
25
0
Order By: Relevance
“…9,22,23 Among them, the orientation-dependent oxidation of Cu substrates under ambient conditions has drawn an increasing attention due to the prospective application of graphene as barrier layers. [24][25][26] Since the pioneering work by Chen et al in 2011, 27 the atomically thick graphene layer has been supposed to be a promising anticorrosion coating owing to its excellent thermal and chemical stability as well as impermeability to molecules. It has been demonstrated that CVD growth graphene can effectively prevent oxidative species reaching the underlying Cu surface and thus protects Cu from being oxidized under ambient conditions for long time (months) 13,25,26 and harsh conditions for short time (hours to days).…”
Section: Chemical Vapor Deposition (Cvd) Growth Graphene On Polycryst...mentioning
confidence: 99%
See 2 more Smart Citations
“…9,22,23 Among them, the orientation-dependent oxidation of Cu substrates under ambient conditions has drawn an increasing attention due to the prospective application of graphene as barrier layers. [24][25][26] Since the pioneering work by Chen et al in 2011, 27 the atomically thick graphene layer has been supposed to be a promising anticorrosion coating owing to its excellent thermal and chemical stability as well as impermeability to molecules. It has been demonstrated that CVD growth graphene can effectively prevent oxidative species reaching the underlying Cu surface and thus protects Cu from being oxidized under ambient conditions for long time (months) 13,25,26 and harsh conditions for short time (hours to days).…”
Section: Chemical Vapor Deposition (Cvd) Growth Graphene On Polycryst...mentioning
confidence: 99%
“…[24][25][26] Since the pioneering work by Chen et al in 2011, 27 the atomically thick graphene layer has been supposed to be a promising anticorrosion coating owing to its excellent thermal and chemical stability as well as impermeability to molecules. It has been demonstrated that CVD growth graphene can effectively prevent oxidative species reaching the underlying Cu surface and thus protects Cu from being oxidized under ambient conditions for long time (months) 13,25,26 and harsh conditions for short time (hours to days). 23,[28][29][30][31] Nevertheless, from the perspective of long-term anti-corrosion performance, graphene coating has been found to accelerate the oxidation of the Cu substrate in ambient atmosphere at room temperature.…”
Section: Chemical Vapor Deposition (Cvd) Growth Graphene On Polycryst...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the conducting graphene layers might accelerate the corrosion in some instances [ 1 ]. Moreover, under ambient conditions, metal crystallographic orientation (especially for copper) is dominant to determine the degree of oxidation of substrate beneath graphene [ 2 ]. Deposition of the impeccable graphene coatings on a metal substrate is a rather challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Braeuninger-Weimer et al have studied the effect of copper crystal orientation on graphene growth and anticorrosive properties. According to the authors, Cu crystal orientations such as (011) exhibiting weak interaction force with graphene cannot prevent the intercalation of corrosive agents, hence resulting into corrosion [ 30 ]. However, copper with crystal orientations as Cu(111)and Cu(311) offer relatively strong interfacial coupling with graphene leading to an improved anticorrosive behaviour [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%